Physiological and biomechanical responses to exercise on two different types of rowing ergometers in NCAA Division I oarswomen - Lu, T.; Jones, M. T.; Yom, J.; Ishida, A.; White, J. B. (European Journal of Applied Physiology, 2023)
Background Stationary (SE) and dynamic (DE) rowing ergometers, that are utilized for indoor training and physical assessment of competitive rowers, may elicit different physiological and biomechanical responses. The present study used SE and DE ergometers to examine submaximal and peak physiological and biomechanical responses during an incremental rowing test.